Bile acid excretion after pull-through operation for Hirschsprung's disease. Issue 3 (March 1975) - Gaze, H; Murphy, G M; Nelson, R; Corkery, J J; Anderson, C M
Abstract : Four children with chronic diarrhoea and perianal excoriation after a pull-through operation for Hirschsprung's disease have been shown to have increased but not markedly raised levels of faecal bile acids. Bile acid analysis of the 'bile-rich' duodenal fluid obtained after pancreozymin stimulation in 3 of the patients indicated a marked reduction in the proportion of deoxycholic acid conjugates. These findings are compatible with colonic malabsorption of secondary bile acids in these patients which is related in some way to the pull-through operation, but which is not likely to be the cause of the diarrhoea and the anal excoriation.